Desa terpen labe meia modi gailemna flu burung lahamna labe iba beom bake soat vatohehe im - Dima, Rudi; Briley, David; Kirihio, Rachfri; Tulahseket, Ishak (SIL International, 2005)
https://www.sil.org/resources/archives/38223